Pengaruh Fasilitas Shopee Paylater dan Promosi Diskon terhadap Perilaku Konsumtif Konsumen Shopee Kelurahan Korpri Jaya Kecamatan Sukarame Bandar Lampung - Selvi Anita; Suradi; Aprilianto Amir (Prodi Administrasi Bisnis FISIP Universitas Tulang Bawang Lampung, 2026)
Shopee PayLater and discount promotions have a significant influence on consumer consumptive behavior. The PayLater feature allows consumers to shop without having to pay directly, increasing purchasing power, but also has the potential to trigger consumptive behavior if not managed properly. Discount promotions can also increase purchasing interest and consumer loyalty, but they need to be balanced with wise financial management to avoid negative impacts. This study aims to: (1) Determine the influence of Shopee PayLater facilities on Shopee consumer behavior, (2) Determine the influence of discount promotions on Shopee consumer behavior, and (3) Determine the influence of Shopee PayLater facilities and discount promotions on Shopee consumer behavior. This research uses a quantitative method with a descriptive approach. The data analysis technique used to test the hypothesis is multiple linear regression analysis. The results of the study indicate that: (1) Shopee PayLater facilities have a positive and significant effect on the consumptive behavior of Shopee consumers in Kopri Jaya, Sukarame, Bandar Lampung. This is evidenced by the t-value of 4.141; significance of 0.000 <0.05; and a regression coefficient of 0.294, (2) Discount Promotions also have a positive and significant effect on the consumptive behavior of Shopee consumers in Kopri Jaya, Sukarame, Bandar Lampung. This is evidenced by the t-value of 7.008; significance of 0.000 <0.05; and a regression coefficient of 0.556, and (3) Shopee PayLater facilities and Discount Promotions have a simultaneous effect on the consumptive behavior of Shopee consumers in Kopri Jaya, Sukarame, Bandar Lampung. This is evidenced by the F-value of 65.552; significance of 0.000 <0.05; and the Adjusted R Square value is 0.568 or 56.8%. In this case, it can be concluded that the Shopee PayLater facility and discount promotions are quite important factors in influencing the consumptive behavior of Shopee consumers. Keywords: consumptive behavior; discount promotions; shopee paylater facility